1999
DOI: 10.1034/j.1600-0412.1999.780910.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of labor with mifepristone, ‐ A randomized, double‐blind study versus placebo

Abstract: The results of the present study show that mifepristone is a simple and effective treatment for inducing labor in post-term women with an unripe cervix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 17 publications
5
31
1
1
Order By: Relevance
“…The median Bishop Score at the start of induction was similar in both groups which was comparable to stenlund et al 12 and Elliot et al 13 During the first 48 hours after the treatment was started 75% women who were given Mifepristone and 48% who were given placebo went into labour which was comparable to Elliot et al 13 and Giacolone et al 14 In Frydman 11 study, spontaneous onset of labour occurred in 31(54%) patients in study group but only in 10(18%) patients in placebo treated females. The number of patients with onset of labour pains within 48 hours of induction was less than the present study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The median Bishop Score at the start of induction was similar in both groups which was comparable to stenlund et al 12 and Elliot et al 13 During the first 48 hours after the treatment was started 75% women who were given Mifepristone and 48% who were given placebo went into labour which was comparable to Elliot et al 13 and Giacolone et al 14 In Frydman 11 study, spontaneous onset of labour occurred in 31(54%) patients in study group but only in 10(18%) patients in placebo treated females. The number of patients with onset of labour pains within 48 hours of induction was less than the present study.…”
Section: Discussionsupporting
confidence: 86%
“…The incidence of nulliparity was 58% in study group and 52% in control group in present study. The distribution of pregnancies and deliveries did not differ significantly between the two groups which was comparable to frydman et al 11 and stenlund et al 12 In study by Mc Gill, 72% patients in each group were nulliparous. In all these studies most of the women who received labour induction were nulliparous.…”
Section: Discussionsupporting
confidence: 81%
“…), genetic syndromes (such as Ehlers-Danlos syndrome) [62], subclinical intra-amniotic infection [63][64][65] or intra-amniotic inflammation [66,67], or the elusive condition referred to as cervical insufficiency [68][69][70]. A decrease in progesterone action has been implicated in untimely cervical ripening [71][72][73][74][75][76][77][78], as this hormone plays a key role in maintaining the cervix as long and closed during pregnancy [77][78][79][80][81][82][83][84][85][86][87][88].…”
Section: Introductionmentioning
confidence: 99%
“…Similar regimens have also been used with moderate success in the management of miscarriage 8,9 . However, to our knowledge there are no reports of the combined treatment in cases of intrauterine death despite significant effects of both drugs on the uterus in late pregnancy 10,11 . This study has demonstrated an effective combined regimen for induction of labour in late fetal death.…”
Section: Discussionmentioning
confidence: 99%